2011
DOI: 10.1021/nn1029845
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Ternary AlGaN Alloy Nanocones across the Entire Composition Range

Abstract: AlGaN ternary alloys have unique properties suitable for numerous applications due to their tunable direct band gap from 3.4 to 6.2 eV by changing the composition. Herein we report a convenient chemical vapor deposition growth of the quasi-aligned Al(x)Ga(1-x)N alloy nanocones over the entire composition range. The nanocones were grown on Si substrates in large area by the reactions between GaCl(3), AlCl(3) vapors, and NH(3) gas under moderate temperature around 700 °C. The as-prepared wurtzite Al(x)Ga(1-x)N n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
(89 reference statements)
2
59
0
Order By: Relevance
“…As one important impurity, oxygen is often unavoidably incorporated in AlN because of the fact that it cannot be totally removed from the growth circumstance and since it has high solubility in AlN. In particular, the optical properties of AlN nanomaterials are much influenced by oxygen‐related defects due to their large surface‐to‐volume ratio . In our case, EDS analysis indicates that there is about 8.46 at.% oxygen incorporated in the product.…”
Section: Resultsmentioning
confidence: 69%
“…As one important impurity, oxygen is often unavoidably incorporated in AlN because of the fact that it cannot be totally removed from the growth circumstance and since it has high solubility in AlN. In particular, the optical properties of AlN nanomaterials are much influenced by oxygen‐related defects due to their large surface‐to‐volume ratio . In our case, EDS analysis indicates that there is about 8.46 at.% oxygen incorporated in the product.…”
Section: Resultsmentioning
confidence: 69%
“…The III-V nitrides, especially gallium nitride (GaN) and its related alloys (e.g.,G a x In 1Àx N, and Ga x Al 1Àx N), have become the subject of intense scientific attention owing to their peculiar physical and chemical properties. [1][2][3][4] More specifically,t hey can be used in gas sensing and bioimaging. [5] GaNcan be used in high-temperaturem icroelectronic and optoelectronic devices because of its hight hermal conductivity ands tability,a nd its direct bandgap( % 3.4 eV at room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] As an alternative path to achieve high efficiency UV LEDs and lasers, AlGaN nanowire structures have drawn considerable attention. [18][19][20][21][22][23][24][25][26][27][28][29][30] The promise of AlGaN nanowires stems not only from their low defect densities, but more importantly, their surface enhanced p-type dopant (Mg) incorporation. It has been demonstrated, both experimentally and theoretically, that Mg-dopant incorporation is significantly enhanced in AlN, InN, and GaN nanowire structures compared to their bulk counterparts, 26,[31][32][33] thereby promising very efficient p-type conduction in wide bandgap Al-rich AlGaN that was not possible previously.…”
mentioning
confidence: 99%
“…However, with the use of conventional chemical vapor deposition processes, Al-rich AlGaN nanowire structures only yield defect-related emissions in the wavelength range >300 nm. [18][19][20][21][22] Recent studies have shown that spontaneously formed AlGaN nanowire heterostructures with significantly improved optical and electrical properties can be realized via catalyst-free molecular beam epitaxy (MBE). [23][24][25][26][27][28][29][30][34][35][36][37][38] wavelengths of LEDs and lasers using such spontaneously formed AlGaN nanowires have been limited to 250 nm, or longer.…”
mentioning
confidence: 99%